1948
DOI: 10.1002/hlca.19480310231
|View full text |Cite
|
Sign up to set email alerts
|

Beitrag zum Problem der Decarboxylierung. 3. Mitteilung. Theoretische Betrachtungen zum Problem der Decarboxylierungsreaktion

Abstract: In der vorliegenden Arbeit berichten wir uber einen Versuch, die bei den vielen Untersuchungen uber die Derarboxylierungsreaktion gewonnenen verschiedenartigen Ergehnisse von einem gemeinsanieii Gesichtspunkt atis zu betrachten. Es wird diesr Reaktion als elektrophile Substitution behandelt, wobei nns die allgemeinen theoretischen Betrachtungen von Hughes und I n g~Z d~)~) und die aus der ,,Theorie der absoluten Reak-tion~geschwindigkeit"~) gewonnenen Ergehnisse als Grundlage dientcn. Versuche zur clektronenth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1952
1952
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…No further spectral change was observed for the cations of either 9-ACA or 9−MCA in concentrated acid solutions, although aromatic carboxylic acids and esters are known to undergo protonation at the carbonyl oxygen near H 0 −8 . The absorption spectrum of 9-AA also does not show any change in the above acidity region, except in concentrated HClO 4 ( H 0 −7.7) where it is reported to undergo decarboxylation to produce anthracene 5 Absorption spectra (long-wavelength band) of the prototropic species of 9-ACA and 9-MCA (insert).…”
Section: Resultsmentioning
confidence: 97%
“…No further spectral change was observed for the cations of either 9-ACA or 9−MCA in concentrated acid solutions, although aromatic carboxylic acids and esters are known to undergo protonation at the carbonyl oxygen near H 0 −8 . The absorption spectrum of 9-AA also does not show any change in the above acidity region, except in concentrated HClO 4 ( H 0 −7.7) where it is reported to undergo decarboxylation to produce anthracene 5 Absorption spectra (long-wavelength band) of the prototropic species of 9-ACA and 9-MCA (insert).…”
Section: Resultsmentioning
confidence: 97%
“…In 1948, Schenkel and Schenkel-Rudin (9) suggested that some organic acids are decarboxylated by a bimolecular electrophilic substitution mechanism (S,2). Since then, several exanlples of S,2 mechanisms have been found (4,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Polyenoic acids could serve as a concealed form of polyenes if mild methods existed for their protodecarboxylation. The existing acid-catalyzed protodecarboxylation methods are not typically compatible with polyenes due to possible polymerization issues . In recent years, metal-catalyzed protodecarboxylations and decarboxylative coupling reactions have received much attention .…”
mentioning
confidence: 99%